Keto-analogues in pre-dialysis Chronic Kidney Disease patients: Review of Old and new data - Liliana Garneata; Gabriel Mircescu (The Korean Society of Nephrology, 2012)
Recently revealed high prevalence of Chronic Kidney Disease (CKD) raises concerns all over the world; evidence based strategies to delay progression were set up. Dietary approach is largely mentioned, but strong evidence is lacking. The reduced dietary protein intake has been reported for more than a century to improve uremic symptoms and even to postpone the initiation of renal replacement therapy (RRT); however, the nutritional intervention in uremia is still under debate. Different dietary protein regimens have been proposed for the CKD patients: (1) conventional low protein diet (LPD), with 0.6 g/kg per day; (2) very low protein diet (0.3 g/kg per day) supplemented with essential amino acids or (3) very low protein diet (0.3 g/kg per day) supplemented with an isomolar mixture of essential amino acids and nitrogen-free keto-analogues (SVLPD). Available data support SVLPD to be effective in ameliorating nitrogen waste products retention, acid-base and calcium-phosphorus metabolism disturbances and insulin-resistance and in delaying the RRT initiation, with no deleterious effect on the nutritional status in CKD patients.More recent studies report that SVLPD could also slow down the rate of decline in renal function, preserving the nutritional status and associating better outcome after the start of RRT. The possible delay of RRT initiation through nutrition could have major impact on patients' quality of life. On the other hand, postponing RRT could have also a serious economic impact, particularly important in countries where the dialysis facilities still do not meet the needs. The nutritional intervention, particularly the SVLPD could be a new link in the RRT integrated care model. However, a careful selection of motivated patients who could benefit from such a diet, close nutritional monitoring and dietary counseling are highly required.